Дослідження методів та моделей розробки ігрового додатку IT-проєкту - Трофімець, І. М. (ХНУРЕ, 2024)
This article (science work) refers to the process of building recommendations by consumers on the choice of goods and services, which are implemented in recommender systems based on taking into account the choice of similar users and the corresponding properties of goods. The peculiarity of such processes is that when building recommendations, the interests of similar users are taken into account, but not enough attention is paid to changes in the patterns of behavior of such users over time.
Keywords: IT-проєкт